Analisis Kandungan Zat Besi (Fe) Pada Buah Kelor dan Daun Kelor (Moringa Oleifera) yang Tumbuh di Desa Matajang Kec. Dua Boccoe Kab. Bone - Andi Nurrahma; Alimin Alimin; Wa Ode Rustiah (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2013)
This research is a kind of experiment research by analyze mineral such as iron essence (Fe) that are needed as a suplement in our body. In this research are used the kelor’s fruits and kelor’s leaf as specimen with the aim to know the iron essence (Fe) that content in the specimen. The content of iron essence (Fe) in specimen are used by Atomic Absorption Spectroscopy (AAS) method. The kelor’s fruits, the average iron essence (Fe) content in A place is 2,50 mg/100 gram specimen, B place is 3,20 mg/100 gram specimen, C place si 3,59 mg/100 gram specimen and D place is 4,51 mg/100 gram specimen. Than the kelor’s leaf, the average iron essence (Fe) content in A place is 5,89 mg/100 gram specimen, B place 5,73 mg/100 gram specimen, C place is 6,02 mg/100 gram specimen and D place is 6,21 mg/100 gram specimen.